2020
DOI: 10.21203/rs.3.rs-69297/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence and associated factors for Alcohol Use Disorder among tuberculosis patients: A systematic review and meta-analysis study.

Abstract: Background: Alcohol use disorders (AUD) in tuberculosis patients are complicated with poor compliance to anti-tuberculosis treatment and poor tuberculosis treatment outcomes. However, aggregate data concerning this problem is not available. Therefore, this review aimed to fill the above gap by generating an average prevalence of AUD in tuberculosis patients.Method: Our electronic search for original articles was conducted in the databases of Scopus, PubMed, and EMBASE, African Index Medicus, and psych-info. Be… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 33 publications
2
4
0
Order By: Relevance
“…Males were more likely to have 'any' psychiatric illness or alcohol and substance use disorders, similar to findings of a meta-analysis [15] and several other studies in Africa and Asia [16][17][18]45]. Culturally, social drinking among men is more tolerated compared to the same in females while it could be the start or gateway to alcohol or substance use disorders.…”
Section: Determinants Associated With Psychiatric Morbiditysupporting
confidence: 83%
See 4 more Smart Citations
“…Males were more likely to have 'any' psychiatric illness or alcohol and substance use disorders, similar to findings of a meta-analysis [15] and several other studies in Africa and Asia [16][17][18]45]. Culturally, social drinking among men is more tolerated compared to the same in females while it could be the start or gateway to alcohol or substance use disorders.…”
Section: Determinants Associated With Psychiatric Morbiditysupporting
confidence: 83%
“…The assessed prevalence of alcohol use disorder is similar to a pooled average of 30% in a meta-analysis of 28 studies in tuberculosis patients [15], but double that previously reported for the general Kenyan population at 13.6% [37]. There's a strong association between heavy alcohol use and TB as alcohol weakens the immune system by interfering with the integrity and microbiomes of the gastrointestinal tract, decreasing and damaging the epithelial cells and by disruption of the ciliary function of the upper airways thus ultimately increasing the risk of TB [38].…”
Section: Plos Onesupporting
confidence: 55%
See 3 more Smart Citations